Simulation of β-Ga2O3 vertical Schottky diode based photodetectors revealing average hole mobility of 20cm2V-1s-1 - Akyol, Fatih (AIP Publishing, 2020)
With a wide bandgap of similar to 4.85eV, high chemical and thermal stability, and melt growth availability, beta-Ga2O3 has been found in a large number of solar blind photodetector (SBP) applications including missile guidance, flame detection, water purification, and intersatellite communication. The modelling of a Schottky diode (SD) based SBPs is crucial in order to reach high external quantum efficiency (EQE), especially for self-powered applications and also to extract hole mobility in these devices. The EQE performance of beta-Ga2O3 vertical SD SBPs with various Schottky contact finger spacings is obtained using highly controversial hole mobility values reported in the literature. By modelling experimentally demonstrated EQE values of the existing beta-Ga2O3 vertical SD SBPs, average nonequilibrium hole mobility value of similar to 20cm(2)V(-1)s(-1) is extracted, which is quite higher than the claimed theoretical value of 1x10(-6)cm(2)V(-1)s(-1) and motivates for the efforts of technologically important p-type beta-Ga2O3. By modelling the efficiency of full Schottky metal covered vertical SD SBPs by using hole mobility value of 20cm(2)V(-1)s(-1), internal quantum efficiency of 92% is obtained at an optimum n-type doping concentration of 1x10(16)cm(-3). Published under license by AIP Publishing.
Keywords: LUMINESCENCE; Physics